2010
DOI: 10.1007/s00122-010-1316-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping of the leaf rust Lr34 locus in Triticum aestivum (L.) and characterization of large germplasm collections support the ABC transporter as essential for gene function

Abstract: Leaf rust resistance gene Lr34 is likely the most important leaf rust gene characterized to date. It has been characterized as an adult plant resistance gene and is known to enhance the resistance of other leaf rust resistance genes and to condition resistance to a number of other diseases. Located on chromosome 7D, this gene was identified to be one of six co-located genes of which, an ABC transporter was shown to be the only valid candidate. Ten new molecular markers were developed spanning the Lr34 locus, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 42 publications
3
64
0
5
Order By: Relevance
“…Alleles of resistant (Lr34res-D) and susceptible (Lr34sus-D) cultivars are characterized by only three mutations ). Only five major Lr34 haplotypes, either representing mutated versions of Lr34res-D or variants of Lr34sus-D, were identified in the wheat gene pool (Dakouri et al 2010(Dakouri et al , 2014Lagudah et al 2009;McCallum et al 2012). A recent study of a collection of 252 accessions of the D-genome progenitor of bread wheat, Aegilops tauschii, revealed very low nucleotide variation in Lr34 (π = 0.0011; Krattinger et al 2013), similar to the results presented here for Yr36.…”
Section: Reduced Genetic Diversity At the Wks1 Locussupporting
confidence: 83%
See 1 more Smart Citation
“…Alleles of resistant (Lr34res-D) and susceptible (Lr34sus-D) cultivars are characterized by only three mutations ). Only five major Lr34 haplotypes, either representing mutated versions of Lr34res-D or variants of Lr34sus-D, were identified in the wheat gene pool (Dakouri et al 2010(Dakouri et al , 2014Lagudah et al 2009;McCallum et al 2012). A recent study of a collection of 252 accessions of the D-genome progenitor of bread wheat, Aegilops tauschii, revealed very low nucleotide variation in Lr34 (π = 0.0011; Krattinger et al 2013), similar to the results presented here for Yr36.…”
Section: Reduced Genetic Diversity At the Wks1 Locussupporting
confidence: 83%
“…The characterization of nucleotide diversity of the leaf rust QR gene Lr34 revealed relatively lowsequence diversity. In the wheat gene pool, two predominant Lr34 alleles (Lr34res-D and Lr34sus-D) were found that differ by only two critical codons in exon 11 and exon 12 (Dakouri et al 2010;Krattinger et al 2009Krattinger et al , 2011Lagudah et al 2009;McCallum et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The tyrosine residue at position 634 of LR34sus-D is highly conserved among different ABCG proteins in various plant species (Krattinger et al 2011). Several additional Lr34 alleles have been identified at lower frequencies in the wheat genepool (Dakouri et al 2010;Lagudah et al 2009;McCallum et al 2012). However, none of these were associated with disease resistance and they either represent In this study we examined Lr34 homoeologs and orthologs in a set of wheat, rice and sorghum genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that developmentally regulated resistance is correlated with elevated Lr34 transcript levels in flag leaves of adult plants. There are several allelic forms of the Lr34 gene that have been identified in the wheat germplasm, with two alleles occurring at a high frequency [6] . Resistance allele (Lr34res) differs by only two amino acid changes from the other allelic forms associated with susceptibility (Lr34sus) and so…”
Section: Introductionmentioning
confidence: 99%